2011
DOI: 10.1063/1.3563016
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Direct angle-resolved measurements of collision dynamics with electronically excited molecules: NO(A2Σ+) + Ar

Abstract: We report direct doubly differential (quantum state and angle-resolved) scattering measurements involving short-lived electronically excited molecules using crossed molecular beams. In our experiment, supersonic beams of nitric oxide and argon atoms collide at 90°. In the crossing region, NO molecules are excited to the A2Σ+state by a pulsed nanosecond laser, undergo rotationally inelastic collisions with Ar atoms, and are then detected 400 ns later (approximately twice the radiative lifetime of the A2Σ+state)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Here we improve and extend on our first study [29] of the DCS for rotationally inelastic collisions of NO(A 2 AE þ ) with Ar. The current study extends the range of NO(A 2 AE þ ) rotational quantum states and compares the observed NO(A 2 AE þ ) þ Ar DCS with full QS calculations on the NO(A 2 AE þ )-Ar PES of Klos et al [33].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Here we improve and extend on our first study [29] of the DCS for rotationally inelastic collisions of NO(A 2 AE þ ) with Ar. The current study extends the range of NO(A 2 AE þ ) rotational quantum states and compares the observed NO(A 2 AE þ ) þ Ar DCS with full QS calculations on the NO(A 2 AE þ )-Ar PES of Klos et al [33].…”
Section: Introductionmentioning
confidence: 87%
“…Excited state vector measurements are challenging, although one approach that has seen considerable recent activity is the laser-based measurement of the removal of rotational angular momentum in a thermal collision bath, and associated theoretical development [24][25][26][27]. The few measurements of differential scattering cross-sections (DCS) for electronically excited species are essentially limited to experiments combining the 'photo-loc' method with optical pumping in a thermal bath to study CN(A 2 Å) þ Ar collisions [28], and our proof-of-concept publication of the technique applied in this current paper [29].…”
Section: Introductionmentioning
confidence: 99%
“…Along with advances in theory, there have been comparable developments in experimental methods for the measurements of state-resolved integral and differential cross sections and the determination of binding energies of van der Waals complexes. [20][21][22][23][24] The comparison of measured and computed properties has provided strong validation for the quality of many computed ab initio PESs.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable progress is being made in this area by several groups using the hexapole state selection to select a single quantum state that can be oriented to the collision, 55,56 using a Stark decelerator that is also a state selector, 57,58 or using the laser preparation of a molecule in an excited state that is aligned by the laser to the relative velocity vector of the collision. [59][60][61][62][63] The applications of velocity map ion/electron imaging are wide ranging and often at the cutting edge of science. The latter claim is supported by the thousands of refereed papers that use VMI, with dozens published in the journals Science or Nature.…”
Section: State-of-the-art and Ultimate Imaging Experimentsmentioning
confidence: 99%